2022
DOI: 10.1900/rds.2022.18.68
|View full text |Cite
|
Sign up to set email alerts
|

1,5-Anhydroglucitol as a Marker of Acute Hyperglycemia in Cardiovascular Events

Abstract: 1,5-anhydroglucitol (1,5-AG) is a biomarker of acute hyperglycemia in diabetology and also in cardiodiabetology. It is used to monitor fluctuating glucose levels. 1,5-AG is a monosaccharide that is biochemically similar to D-glucose and originates from the nutrition. The presence of 1,5-AG in blood and tissue is nearly constant due to reabsorption in the renal proximal tubule. In acute hyperglycemia, renal reabsorption is inhibited by glucose and 1,5- AG is excreted in the urine, while its serum level decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…Myo-Inositol was associated with antidepressant activity in experimental models of depression and a possible role in stress resistance pathways evidenced in studies with plants 50,51 . The 1,5-Anhydroglucitol is an important substance with potential use for monitoring glycemic control, and may also interfere with cardiovascular risk 52 . Lastly, D-ribose is used as an anti-fatigue medication and appears to have a role in improving the quality and life expectancy of diabetic patients 53 .…”
Section: Phytochemical Evaluation and Gc-ms Resultsmentioning
confidence: 99%
“…Myo-Inositol was associated with antidepressant activity in experimental models of depression and a possible role in stress resistance pathways evidenced in studies with plants 50,51 . The 1,5-Anhydroglucitol is an important substance with potential use for monitoring glycemic control, and may also interfere with cardiovascular risk 52 . Lastly, D-ribose is used as an anti-fatigue medication and appears to have a role in improving the quality and life expectancy of diabetic patients 53 .…”
Section: Phytochemical Evaluation and Gc-ms Resultsmentioning
confidence: 99%
“…Metabolomics studies have shown that saliva 1,5-AG levels correlate with those in blood, inversely related to blood glucose levels. This makes saliva 1,5-AG a potential non-invasive biomarker for T2D diagnosis (Migała et al, 2022). In urine, metabolites such as 5′-MTA have shown significant changes in late-onset T2D compared to non-diabetic individuals, suggesting their potential as validated biomarkers for T2D.…”
Section: Metabolomics In Type 2 Diabetes Mellitus Researchmentioning
confidence: 99%